1999
DOI: 10.1063/1.123852
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature visible and infrared photoluminescence from Pr-implanted GaN films by focused-ion-beam direct write

Abstract: Rare earth focused ion beam implantation utilizing Er and Pr liquid alloy ion sources

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…While interest in the past focused mostly on infrared applications, especially Er-doped GaN devices emitting at 1.54 µm, it has been shown recently that electroluminescence in the red, green and blue can be produced by doping GaN with Eu [2], Er [3], and Tm [4], respectively. Photo-and electroluminescence in the red region of the spectrum (650 nm) was also obtained from praseodymium (Pr) doped GaN [5][6][7]. Cathodoluminescence in the visible region of the spectrum has been observed from GaN doped with Dy, Er, Tm [8] and Sm or Ho [9].…”
Section: Introductionmentioning
confidence: 99%
“…While interest in the past focused mostly on infrared applications, especially Er-doped GaN devices emitting at 1.54 µm, it has been shown recently that electroluminescence in the red, green and blue can be produced by doping GaN with Eu [2], Er [3], and Tm [4], respectively. Photo-and electroluminescence in the red region of the spectrum (650 nm) was also obtained from praseodymium (Pr) doped GaN [5][6][7]. Cathodoluminescence in the visible region of the spectrum has been observed from GaN doped with Dy, Er, Tm [8] and Sm or Ho [9].…”
Section: Introductionmentioning
confidence: 99%
“…While most studies before 1998 reported only results for the temperature range below 1000°C, newer work focuses increasingly on temperatures at 1100°C and above. Three papers have investigated whether the luminescence intensity of implanted GaN:Er depends on the type of starting material, and found no striking differences between MBE, HVPE or MOCVD GaN [20,22,36].…”
Section: Optical Activationmentioning
confidence: 99%
“…1(b)). Additional emission lines were noted at 1108, 1145, and 1185 nm, but the origin of these lines has not yet been identified [11][12][13]. A schematic energy level diagram of Pr 3+ depicting all identified PL lines is shown in Fig.…”
Section: Methodsmentioning
confidence: 97%
“…There are several reports regarding photoluminescence (PL), electroluminescence (EL), and cathodoluminescence (CL) in the red spectral region from Pr 3+ doped GaN films grown by ion implantation, solid source MBE, and metal-organic chemical vapor deposition (MOCVD) [11][12][13][14][15][16][17][18][19] [16]. Effects of the oxygen incorporation and thermal annealing on the red PL intensity of Pr implanted GaN samples were investigated by Zavada et al [13] and others [17,19].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation